Nutrition and Reproductive Health: Sperm versus Erythrocyte Lipidomic Profile and ω-3 Intake - Gabriela Ruth Mendeluk; Mariano Isaac Cohen; Carla Ferreri; Chryssostomos Chatgilialoglu (Journal of Nutrition and Metabolism)
Fatty acid analyses of sperm and erythrocyte cell membrane phospholipids in idiopathic infertile patients evidenced that erythrocyte contents of EPA, DHA, omega-6–omega-3 ratio and arachidonic acid provide a mathematical correspondence for the prediction of EPA level in sperm cells. The erythrocyte lipidomic profile of patients was significantly altered, with signatures of typical Western pattern dietary habits and no fish intake. A supplementation with nutritional levels of EPA and DHA and antioxidants was then performed for 3 months, with the follow-up of both erythrocyte and sperm cell membranes composition as well as conventional sperm parameters. Some significant changes were found in the lipidomic membrane profile of erythrocyte but not in sperm cells, which correspondently did not show significant parameter ameliorations. This is the first report indicating that membrane lipids of different tissues do not equally metabolize the fatty acid elements upon supplementation. Molecular diagnostic tools are necessary to understand the cell metabolic turnover and monitor the success of nutraceuticals for personalized treatments.